Burden of malnutrition and anemia among children with congenital heart disease - Rabiya, Nargis; E., Elizabeth K.; Masaraddi, Sanjay K.; K., Rugmini (International Journal of Contemporary Pediatrics, 2020)
Background: Congenital heart disease (CHD) is the most common birth defect and in India, the prevalence is 2.5 to 5/1000 live births. Malnutrition and anemia are common co-morbidities, that determine the outcome in CHD. This study was undertaken to assess the extent of malnutrition and anemia among 1-12-year-old children with CHD. Methods: A total 80 children with CHD, admitted for intervention under the Rashtriya Bal Swasthya Karyakram (RBSK) scheme were enrolled. Nutritional status was assessed using standardized anthropometric measurements. Anemia was estimated using hemoglobin, red cell indices, red cell distribution width and peripheral smear. IEC approval, informed consent and assent from participants were obtained prior to the study. Statistical analysis was performed using SPSS version 19. Results: 2/3rd children were >5-years-old. Acyanotic CHD was more common (81.3%) and 35% had ventricular septal defect. Among cyanotic CHD (18.7%), 13.7% had tetralogy of fallot. In CCHD, there was only one child with normal weight and height. In ACHD, 71% were underweight, 49%, had stunting and 82% had wasting. Anemia was diagnosed in nearly 1/3rd, and iron deficiency was the most common. Even though polycythemia was noted in those with CCHD, increased RDW and reduced red cell indices unmasked iron deficiency. Conclusions: Majority were >5-years-old, due to late referral for intervention. The burden of malnutrition and iron deficiency anemia, that modify the outcome, was very high, Hence, early identification, prompt referral and correction of co-morbidities are of utmost importance, as majority are likely to get surgical/non-surgical interventions under government sponsored schemes like RBSK in India.